Block of c-Fos and JunB expression by antisense oligonucleotides inhibits light-induced-phase shifts of the mammalian circadian clock - Wollnik, Franziska; Brysch, W.; Uhlmann, E.; Gillardon, Frank; Bravo, R.; Zimmermann, M.; Schlingensiepen, K. H.; Herdegen, Thomas (European journal of neuroscience, 1995)
Light-induced phase shifts of circadian rhythmic locomotor activity are associated with the expression of c-Jun, JunB, c-Fos and FosB transcription factors in the rat suprachiasmatic nucleus, as shown in the present study. In order to explore the importance of c-Fos and JunB, the predominantly expressed AP-1 proteins for the phase-shifting effects of light, we blocked the expression of c-Fos and JunB in the suprachiasmatic nucleus of male rats, housed under constant darkness, by intracerebroventricular application of 2 μ1 of 1 mM antisense phosphorothioate oligodeoxynucleotides (ASO) specifically directed against c-fos and JunB mRNA. A light pulse (300 lux for 1 h) at circadian time 15 induced a significant phase shift (by 125 ± 15 min) of the circadian locomotor activity rhythm, whereas application of AS0 6 h before the light pulse completely prevented this phase shift. Application of control nonsense oligodeoxynucleotides had no effect. ASO strongly reduced the light-induced expression of c-Fos and JunB proteins. In contrast, light pulses with or without the control nonsense oligodeoxynucleotides evoked strong nuclear c-Fos and JunB immunoreactivity in the rat suprachiasmatic nucleus. These results demonstrate for the first time that inducible transcription factors such as c-Fos and JunB are an essential part of fundamental biological processes in the adult mammalian nervous system, e.g. of light-induced phase shifts of the circadian pacemaker.
Gesehen am 14.08.2025